Muhammad Abduh’s influence in Southeast Asia - Amir, Ahmad N.; Shuriye, Abdi Omar; Daoud, Jamal Ibrahim (IDOSI, 2013)
Muhammad Abduh had a remarkably profound and lasting impact in South East Asia. His works and ideaswerehighly influential in the region with strong repercussion in itspolitical and social landscape. He had strongly impacted the movements of Muhammadiyah, al-Irshad and Persatuan Islam(Persis). HisTafsir al-Manar,had powerfully influencedTafsir al-Azhar, Tafsir al-Qur’an al-Karim, Tafsir al-Qur’an al-Madjid (Tafsir al-Nur), Tafsir al-Quran al-Hakim, Tafsir al-Misbah,and Tafsir al-Furqan. The Majallat al-Manarinitiated by Muhammad Abduhhad significantly inspired many reform oriented works such asjournalal-Munir, al-Imam, Saudara, al-Ikhwan, al-Dhakhirah al-Islamiyahand Seruan Azhar. Thus, this paper will attemptto survey Abduh’s extensive influence andits impact on Islamic reform (tajdid)in the Malay Archipelago.